Evaluating the Proximate Analysis, Antioxidant Activity and Probiotic Viability of Smoked Banana Probiotic Leather - Yahya, H. N; L. Karim; N. Yahaya; Izalan, H. S; Hafiza Yahya (SASPR Edu International Pvt. Ltd, 2026)
Non-Indexed Publication